The Divine Comedy: Volume 1: Inferno - Dante Alighieri; Translated By Mark Musa (London Penguin Books, 1984)
This splendid verse translation by Allen Mandelbaum provides an entirely fresh experience of Dante's great poem of penance and hope. As Dante ascends the Mount of Purgatory toward the Earthly Paradise and his beloved Beatrice, through "that second kingdom in which the human soul is cleansed of sin, " all the passion and suffering, poetry and philosophy are rendered with the immediacy of a poet of our own age. With extensive notes and commentary prepared especially for this edition.
Include Illustrations
Keywords: Inferno (Dante Alighieri) -- Dante Alighier